« Détruire » disent-ils… Violence et mystique dans Thirteen Cents et Les Villes assassines - Tina Harpin (Itinéraires, 2016)
If the postcolonial city characterized by its movement provides hope for many writers and thinkers, it also persists as the gloomy muse that inspires an existential questioning of the meaning of life. In this article, I examine the issues at stake in the tragic poetics of the city in motion in the novels Thirteen Cents by Sello K. Duiker (2000) and Les Villes assassines by Alfred Alexandre (2011) and explain the element of mysticism at the heart of the depiction of violence embodied by menial and marginalized characters who have no choice but to voice their will to destroy.